Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan dan Struktur Aktiva Terhadap Struktur Modal Pada Perusahaan Property dan Real Estate - Indah Haryati; Muhammad Rosidi (Universitas Sains dan Teknologi Komputer, 2023)
The research aimed to return on asset, current ratio, company size and assets structure on capital structure at property and real estate companies in indonesia stock exchange year of 2020-2022. The selected sample were 64 companies through purposive sampling. Souurces of data used secondary data with data collection through documentation. The data analysis technique used multiple linear regression. The results showed that the return on asset has a positive and signification effect on capital structure. Current ratio has a negative and signification effect on capital structure. Company size does not have a signification effect on capital structure. Asset structure has a positive and signification effect on capital structure.